Daily behaviour of Hungarian Grey Cattle under range grazing conditions - Halász, András; Nagy, Géza (Acta Agraria Debreceniensis, 2013)
Cattle behaviour on rangeland depends on external factors, such as grass allowance and quality, temperature, net solar radiation, distance from water-source, wind speed and direction, air pressure changes and the applied breeding technology. Our research is based on previous empirical observations and modern methods to analyze the behaviour of the Hungarian Grey Cattle. Today it is crucial to use cost-effective solutions in modern beef cattle farming therefore we introduce a cost-efficient method to study and follow cattle herds. We are studying relation between traveled daily distance and air pressure. The various weather fronts influence behavioural characteristics and traveled daily distance. According to our hypothesis, the pressure-change and the wind direction has significant effect on cattle activity on pasture. As the different air masses alter the barometric conditions and unbalance the neuroendocrine system, indirectly cause relaxed or agitated behaviour